2006
DOI: 10.1007/s00595-006-3262-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Repair of Gastric Volvulus Associated with Wandering Spleen in an Adult: Report of a Case

Abstract: Gastric volvulus is an uncommon entity that may rapidly progress to infarction and necrosis of the stomach. We herein report the case of a 67-year-old man with acute gastric volvulus in association with wandering spleen. Following a reduction of the volvulus with a nasogastric tube, laparoscopic gastropexy was performed. Pediatric cases of gastric volvulus and a concurrent wandering spleen have been described, but to the best of our knowledge, no adult cases have previously been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
7
0
4
Order By: Relevance
“…These operative findings are similar to those of wandering spleen and intestinal malrotation. After extensive literature search the authors found only one case of MA volvulus secondary to acquired wandering spleen in an adult; however, there were no other reported cases of a patient with global absence of colonic and splenic ligamentous attachments causing gastric volvulus in an adult over the age of 30 years 7. This unique finding is consistent with a large study looking at cases of intestinal obstruction secondary to congenital abnormalities, which showed a significant tail-off in numbers over the age of 12 years 8.…”
Section: Discussionmentioning
confidence: 99%
“…These operative findings are similar to those of wandering spleen and intestinal malrotation. After extensive literature search the authors found only one case of MA volvulus secondary to acquired wandering spleen in an adult; however, there were no other reported cases of a patient with global absence of colonic and splenic ligamentous attachments causing gastric volvulus in an adult over the age of 30 years 7. This unique finding is consistent with a large study looking at cases of intestinal obstruction secondary to congenital abnormalities, which showed a significant tail-off in numbers over the age of 12 years 8.…”
Section: Discussionmentioning
confidence: 99%
“…Gezici dalağa bağlı gastrik volvulus ise çok nadir görülmektedir. İlk tanımlandığı 1994 yılından şu ana kadar saptanan 31 olgunun sadece ikisi erişkin yaş (23 ve 67 yaş) grubundadır [1,2,12]. Diğer hastaların hepsi 12 yaş ve altındadır [12][13][14][15][16].…”
Section: Discussionunclassified
“…Diğer hastaların hepsi 12 yaş ve altındadır [12][13][14][15][16]. Erişkin hastalardan birisi abdominal distansiyon ve kusma yakınmalarıyla hastaneye başvurmuştur [2]. Diğer hasta ise gastrosplenik ligamandaki varislerin yol açtığı üst gastrointestinal kanama şikayetiyle hastaneye başvurmuştur [1].…”
Section: Discussionunclassified
See 2 more Smart Citations